Submucosal Colonic Lipoblastoma Presenting With Colo-colonic Intussusception in an Infant. (July 2018) - Brundler, Marie-Anne; Kurek, Kyle C; Patel, Kamlesh; Jester, Ingo
Lipoblastoma is a benign adipose tumor typically presenting in infancy in superficial soft tissues of extremities. Intestinal complications secondary to intraabdominal or retroperitoneal involvement are exceedingly rare. We describe a unique case of a primary intestinal lipoblastoma arising from the submucosa of the transverse colon in an otherwise healthy 18-month-old boy. He presented with a history of reducible rectal prolapse, rectal bleeding, and episodic abdominal pain and was initially treated for constipation. Imaging identified a short colo-colonic intussusception, confirmed at laparotomy, and a fatty mass thought to arise from the mesentery. Pathological examination of the resected transverse colon revealed a submucosal tumor composed of a mixture of mature adipose tissue, foci of myxoid mesenchymal tissue with desmin positive, HMGA2 negative spindle cells, and scattered lipoblasts, characteristic of lipoblastoma. Lipoblastoma should be considered as a potential albeit rare cause of intussusception in young children, where a pathologic lead point is infrequently identified.